SEJARAH DAKWAH DI LEMBAH PALU - Syamsuri Syamsuri (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
There are three phases of the spread and development of Islam in Palu: mythological, ideological and scientific phases. In this paper, the figures of these three phases will be discussed. At this phase, the approach of Muslim scholars (ulama is to show natural symbols in spreading and teaching Islam. Spiritual power becomes a key of the success of ulama. There are three ulama who play a role in a mythological phase, Abdullah Raqi "Datuk Karama", a son of Minangkabau coming to Palu in 1650. He was followed by Pue Imbatu "Syekh Lokiya", a native Muslim scholar, and then followed by Daeng Konda "Pue Bulangisi", a noble man who is popular with his teaching "karaeng". This teaching refers to a leading figure Syekh Yusuf Tuanta Salamaka Tajul Khalwati, a national hero of South Africa and Indonesia